217k views
5 votes
(78 - x) + ( 84 - 3x)

User Kroksys
by
5.0k points

2 Answers

3 votes
78-x+84-3x calculate that and you get
162-4x
User Paskas
by
5.8k points
5 votes

Hey there!


(78 - x) + (84 - 3x)

= 78 - x + 84 - 3x

= 78 - 1x + 84 - 3x

= (78 + 84) - (1x - 3x)

= (78 + 84) - (x - 3x)

= (1x - 3x) + (78 + 84)

= (x - 3x) + (78 + 84)

= x - 3x + 78 + 84

= -4x + 162


Therefore, your answer should be:

-4x + 162


Good luck on your assignment & enjoy your day!


~Amphitrite1040:)

User Damianodamiano
by
5.3k points